The experiences of parents in mindfulness-based cognitive therapy. - Bailie, C; Kuyken, W; Sonnenberg, S (2012)
Mindfulness-based cognitive therapy (MBCT) is a relatively new intervention that has been developed to help people with recurrent depression stay well in the long term. Although there is evidence that depression impacts negatively on parenting, little is known regarding MBCT's potential impact on parenting. This study used a qualitative design to explore how parents with a history of recurrent depression experience their relationships with their children one year after MBCT. We interviewed 16 parents who had participated in MBCT as part of a randomized controlled trial (RCT) (Kuyken et al., 2008). Thematic analysis was used to identify prevalent themes in parents' accounts, including: (i) emotional reactivity and regulation; (ii) empathy and acceptance; (iii) involvement; (iv) emotional availability and comfort; and (v) recognition of own needs. Based on these exploratory findings, we suggest that some components of MBCT may help parents with a history of depression with emotional availability, emotion regulation and self-care and set out avenues of further research.